A Simple, Rapid, and Cost-Effective Method for Assessing Carbohydrate Partitioning in Microalgae and Arabidopsis thaliana - Araceli Bader; Lara Rizza; María De Marco; Ana Lando; Giselle Martínez-Noël; Verónica Consolo; Leonardo Curatti (Bio-Protocol)
Carbohydrates serve crucial functions in most living cells, encompassing structural and metabolic roles. Within the realms of plant and algal biology, carbohydrate biosynthesis and partitioning play pivotal roles in growth, development, stress physiology, and various practical applications. These applications span diverse fields, including the food and feed industry, bioenergetics (biofuels), and environmental management. However, existing methods for carbohydrate determination tend to be costly and time-intensive. In response to that, we propose a novel approach to assess carbohydrate partitioning from small samples. This method leverages the differential solubility of various fractions, including soluble sugars, starch, and structural polymers (such as cellulose). After fractionation, a straightforward spectrophotometric analysis allows for the quantification of sugars.